Tingkat Serangan Grayak Spodoptera litura Pada Cabai Rawit (Capsicum frutescens) Dengan Pemberian Bakteri Lysinibacillus sphaericus - Cahyamurti, Riza Afifah; Purwanto, Hari (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
Indonesia is the fourth largest chili producer in the world. In 2017, chili (Capsicum frutescens) was ranked fifth as the largest seasonal vegetable commodity products. The productivity of chili cultivation in Indonesia is hampered by pests and diseases. One of the most common pests that attack chili plants is the armyworm Spodoptera litura (Lepidoptera: Noctuidae). Lysinibacillus sphaericus bacteria have the potential as Plant Growth Promoting Rhizobacteria (PGPR) as well as a bio control agent. This study aims to obtain L. sphaericus isolates that can increase the growth of chili and to determine the effect of L. sphaericus isolates which have the potential for PGPR on the growth of the armyworm feeding on the chili plants. The research method used is experimental research conducted at the Laboratory of Entomology and Sawitsari Research Station, Universitas Gadjah Mada. This study used three replicate by inoculating one millilitre per plant. The results obtained from testing the 105 isolates in the collection of the Faculty of Biology, Universitas Gadjah Mada showed that the isolates that can increase the growth of chili plant indicated with its plant height, were isolates A42, A49, A19, A5, and A38. While the results of plant with the highest number of leaves showed the isolates A49, A42, A19, A38, and A28 were the best among the isolates tested. Some L. sphaericus isolates could increase plant growth compared to the control, but not statistically significant. These bacteria by inoculating one mililitre to plant could not be used as a bio control agent inÂ S. litura because they did not have a significant different in leaf damage to the control.